Compressibility and equivalent bulk modulus of shelled corn. (December 2015) - Cheng, Xuduo; Zhang, Qiang; Yan, Xiaojie; Shi, Cuixia
Abstract : An oedometer was used to measure changes in bulk density of shelled corn at different compression pressures and moisture contents. An equivalent confining pressure (ECP) was introduced to quantify the compression action in grain bins by considering non-uniformity and variability of compression pressures. Two models were developed for predicting bulk density and bulk modulus, respectively, as functions of ECP and moisture content. It was found that the uncompressed bulk density of shelled corn (before applying compression pressure) decreased with grain moisture and the relationship could be adequately described by a linear equation in the moisture range from 12.6 to 17.1% wb (wet basis). Shelled corn was more compressible at higher moisture content. However, bulk density approached to the same maximum value as compression pressure increased regardless of moisture content. In other words, moisture content had little effect on the maximum compressed bulk density. The equivalent bulk modulus of shelled corn increased with compression pressure and decreased with moisture content. The predicted bulk density and bulk modulus values were in good agreement with the experimental data. Highlights: Oedometer tests were conducted to study the compressive behaviour (compressibility) of shelled corn at different moisture contents. Two models were developed to predict compressive behaviour of shelled corn. Shelled corn had lower uncompressed bulk density and was more compressible at higher moisture content. Bulk density approached to the same maximum value as compression pressure increased regardless of moisture content. The proposed models adequately predicted the compressive behaviour of shelled corn.